Relationships Between the Level of Social Competence and Work-Related Behaviors in a Group of Physicians, Nurses, and Paramedics - Bożena, Mroczek; Artur, Kotwas; Iwona, Ewa Karpeta-Pawlak; Weronika, WoliÅ„ska; Jacek, Rudnicki; Magdalena, Bikowska; Donata, Kurpas (International Journal of Psychotherapy Practice and Research, 2017)
The functioning of medical professionals in their work environment is determined by many factors, among them social competence. The Aim of this Study was toanalyze how social competence is related to behaviors and experiences in the context of burnout syndrome, experienced by physicians, nurses, and paramedics in Poland with regard to sociodemographic factors. Methods. The study was conducted in 2015-2016. It involved 432 medical workers, including 29.7% physicians, 36.96% nurses, and 33.3% paramedics. The median age was 38.00. Over half (38.9%) of those surveyed were employed in hospitals, 6.9% in primary care centers, 18.3% in emergency ambulance service. The Social Competence Questionnaire (SCQ), the Work-Related Behaviour and Experience Patterns - AVEM questionnaire, and a self-developed questionnaire were applied. Results. Symptoms of burnout syndrome (Type B and A) were observed in one-fourth of medical workers. 31.8% of all participants presented Type G (p < 0.0001). Behavior types prevailing in particular groups were as follows: paramedics ― Type G and Type S; physicians ― Type A and Type B, and nurses ― Type B and Type G. The general competence level correlated with Type G (p = 0.05), and I competence correlated negatively with Type B (p = 0.02). Conclusions: The problem of burnout syndrome, diagnosed on the basis of work-related behaviors and experiences, is weighty and requires implementation of holistic therapeutic and prophylactic solutions addressed to healthcare professionals. Competence in intimate and social exposure situations, as well as competence in situations requiring assertiveness significantly protect medical workers against burnout syndrome.
Keywords: social competence; job burnout; work-related behavior; physician; nurse; paramedic; SCQ; AVEM; healthcare